(untitled) (Texas Journal of Agriculture and Biological Sciences, 2024)
Light gray stony soils of Namangan region Albit stimulator 75 ml/t per seed before planting and 40 ml/ha during weeding and Gummi 20 stimulator 1.0 l/t per seed before planting and 1.0-1.5 l/ha during weeding-flowering periods when processed according to standards, the field germination rate of the seed is accelerated by 7.5-9.0%, sprouts germinated 1-2 days earlier and plant height is 7.6-11.7 cm, harvested branches are 1.3-1.8 pieces, total formed pods 1.4-1.8 grains, opening of bolls increased by 3.3-5.0%, additional cotton yield increased by 3.3-5.2 tons/ha.